2018
DOI: 10.13189/ujph.2018.060406
|View full text |Cite
|
Sign up to set email alerts
|

Level of Parent Adolescent Communication on Sexual and Reproductive Health Issues and Associated Factors among Debre Markos Preparatory School Students, in Debre Markos Town, East Gojjam, Zone, Ethiopia

Abstract: Background: World Health Organization defines adolescents as those in the age group of 10-19. While parent-adolescent sexual and reproductive health communication is one potential source of sexual and reproductive health information for adolescents. But, it appears to be inadequately practiced in Ethiopia. Objective: To assess level of parent adolescent communication on sexual and reproductive health issues and associated factors among Debre Markos preparatory school students in Debre Markos Town, East Gojjam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
1
17
0
2
Order By: Relevance
“…However, a few adolescents reported they have had SRH discussions with their mothers; though not statistically significant, more girls reported having had this discussion with mothers, compared to boys. Studies on parentchild communication have reported mothers as the usual (sometimes only) source of parental communication about SRH matters [4,18]. In-depth exploration of the contents and triggers of parent-child communication revealed that discussions often centred on pubertal changes, relationship with opposite sex, abstinence from premarital sex, and teenage pregnancy and abortion, and were triggered by environmental factors such as unpleasant or tragic occurrences in the community and parental observations of budding relationships between adolescents of opposite sex.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few adolescents reported they have had SRH discussions with their mothers; though not statistically significant, more girls reported having had this discussion with mothers, compared to boys. Studies on parentchild communication have reported mothers as the usual (sometimes only) source of parental communication about SRH matters [4,18]. In-depth exploration of the contents and triggers of parent-child communication revealed that discussions often centred on pubertal changes, relationship with opposite sex, abstinence from premarital sex, and teenage pregnancy and abortion, and were triggered by environmental factors such as unpleasant or tragic occurrences in the community and parental observations of budding relationships between adolescents of opposite sex.…”
Section: Discussionmentioning
confidence: 99%
“…e caretakers failed to communicate to their adolescent children sensitive topics such as on condoms and contraception and did so on less sensitive topics such as abstinence. Additionally, the pattern of communication varied across the genders of the caretakers/parents and that of the adolescents and depended on the nature of the relationship shared between the two [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of included studies : Full-text cross-sectional articles written in English and published from 2000–2019 were studied in a different part of Ethiopia; of twenty studies, 6 (30%) of them were done in Amhara region ( 12 , 14 , 16 , 19 , 20 , 28 ), 5 (25%) in Southern Nation Nationality People Region (SNNPR) ( 21 , 24 , 26 , 30 , 31 ), 3(15%), 3(15%) in Oromia region ( 11 , 23 , 27 ), 3(15%) in Tigray ( 22 , 25 , 29 ), 2(10%) in Harar region ( 15 , 17 ), 1(5%) in Benishangul Gumuz region ( 18 ) and 1(5%) in Dire Dawa ( 13 ). In the included articles, 14 articles were school-based cross-sectional studies whereas 6 of them were community-based cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Parents-adolescents communication on sexual and reproductive health issues : In most reviewed studies, the level of adolescent-parent communication on SRH issues was dominantly reported within the ranges from 25.3% to 36.9% ( 11 15 , 17 19 , 21 , 24 , 28 – 30 ). In one study, the level of communication on the SRH issue was high which accounted for 82.7% ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation